Cs2SnCl6: To Emit or to Catalyze? Te4+ Ion Calls the Shots - Haiwen Wei; Jikai Sun; Xin Mao; Honglei Wang; Zhen Chen; Tianxin Bai; Pengfei Cheng; Ruiling Zhang; Bing Jin; Panwang Zhou; Feng Liu; Keli Han (Advanced Science)
Abstract A low concentration of Te4+ doping is found to be capable of endowing the lead‐free Cs2SnCl6 perovskites with excellent photoluminescence quantum yield (PLQY), while further increasing Te4+ concentration leads to PLQY deterioration. The mechanism behind the improved PLQY is intensively studied and reported elsewhere. However, little work is conducted to understand the decreased PLQY at high doping levels and to explore its implications for non‐PL‐related applications. Here, it is demonstrated that the Te4+‐incorporated Cs2SnCl6 can be promising candidate for efficient CO2 photocatalysis. An optimum photocatalytic performance is achieved when Te4+ concentration reaches as high as 50%, at which point significant PL quenching has occurred. Through a detailed spectral characterization, such concentration‐dependent functionality is attributed to systematic changes in both electronic and local crystal structure, which allow a robust regulation of excitation energy relaxation channels. These findings expand the scope of available photocatalysts for CO2 reduction and also inform synthetic planning for the preparation of multifunctional Pb‐free metal halide perovskites.